ARTIFICIAL INTELLIGENCE IN THE AUSPICES OF LAW: A DIVERGE PERSPECTIVE - Hasibuan, Rangga Hotman; Aurelya Jessica Rawung; Denisha M. D. Paranduk; Fidel Jeremy Wowiling (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract Artificial Intelligence (AI), encompassing computation for perception, reasoning, and action, poses complex legal considerations. This study explores AI’s impact and its legal ramifications, particularly its autonomy in communication and creation, raising concerns about language, intellectual property, and ethical accountability. Influenced by Common Law and Civil Law systems, discussions vary. Evaluating AI creator liability uncovers intricate connections between AI’s autonomy, intentionality, and creators’ roles. The approach used in this article are based on normative method with multidisciplinary discipline. The results are that though AI creators aren’t directly liable, vicarious liability could link actions to AI behaviors based on programming choices. Balancing innovation and accountability calibrated “creator immunities” are vital. Unchecked immunities could impede responsible AI development; measured immunities might encourage ethical practices, considering AI nuances and societal impacts. Positioning AI as a legal subject necessitates tailored approaches within ethical boundaries. The proposition of AI as a derivative legal subject while setting clear limits is pivotal. Adapting legal systems to evolving AI landscapes and reconciling advancement with societal well-being, is crucial. AI’s intricate accountability, its legal standing, and creator liabilities and immunities demand reshaping legal frameworks for an ethical AI environment. Abstrak Kecerdasan Buatan (AI), yang mencakup komputasi persepsi, penalaran, dan tindakan, menimbulkan pertimbangan hukum yang kompleks. Studi ini mengeksplorasi dampak AI dan konsekuensi hukumnya, terutama otonominya dalam komunikasi dan kreasi, yang menimbulkan kekhawatiran tentang bahasa, kekayaan intelektual, dan akuntabilitas etis. Melalui sistem Common Law dan Civil Law, pembahasannya pun beragam. Mengevaluasi pertanggungjawaban pencipta AI mengungkap hubungan yang rumit antara otonomi, kesengajaan, dan peran pencipta AI. Pendekatan yang digunakan didasarkan pada metode normatif dengan disiplin ilmu yang beragam. Hasilnya adalah bahwa meskipun pencipta AI tidak bertanggung jawab secara langsung, doktrin vicarious liability dapat menghubungkan tindakan dengan perilaku AI berdasarkan pilihanpemrograman. Menyeimbangkan inovasi dan akuntabilitas, kekebalan pencipta yang terukur sangat penting. Kekebalan yang tidak terkendali dapat menghambat pengembangan AI yang bertanggung jawab; kekebalan yang terukur dapat mendorong praktik-praktik etis, dengan mempertimbangkan nuansa AI dan dampak sosial. Memosisikan AI sebagai subjek hukum memerlukan pendekatan yang disesuaikan dengan batasan etika. Proposisi AI sebagai subjek hukum turunan sambil menetapkan batasan yang jelas sangat krusial. Mengadaptasi sistem hukum dengan lanskap AI yang terus berkembang dan menyelaraskan kemajuan dengan kesejahteraan masyarakat, sangatlah vital. Pertanggungjawaban AI yang rumit, kedudukan hukumnya, dan kewajiban serta kekebalan pencipta menuntut pembentukan kembali kerangka kerja hukum untuk lingkungan AI yang etis.